A Study on the Implementation of the Talqin, Tasmi’, Tafahum, Tikrar, and Murajaah Method in Qur’an Memorization Learning at SMA Islam Al-Ulum Terpadu Medan - Sri Wulan Dari (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the implementation of the Talqin, Tasmi’, Tafahum, Tikrar, and Murajaah method in Qur’an memorization learning at SMA Islam Al-Ulum Terpadu Medan. This 3T + 1M method is considered a comprehensive approach that enhances the students’ accuracy, retention, and understanding of Qur’an memorization. The research employs a qualitative field study design involving tahfiz teachers, students, and supporting documentation of the tahfiz program. Data collection techniques include observation, in-depth interviews, and documentation. The findings reveal that the Talqin method helps students acquire correct recitation from the beginning, Tasmi’ strengthens their ability to present memorized verses, Tafahum promotes deeper comprehension of the verses, Tikrar accelerates the memorization of new passages, and Murajaah maintains long-term retention. Overall, the implementation of this method is effective and significantly contributes to improving students’ Qur’an memorization quality. The study highlights the importance of structured and systematic strategies in tahfiz learning.